Islamization of Science: Exploring Seyyed Hossein Nasr's Perspective on Building a Bridge between Science and Faith - Lestari, Ana; Amrillah, Rizki; Agustina, Fahimma Arra; Indra, Ghaida (Holistic Science, 2024)
The Islamization of science is an effort undertaken by Muslim scholars to integrate Islamic values into modern scientific knowledge. This initiative emerged as a response to the dominance of the secular paradigm in science, which often separates rationality from spirituality. This study aims to analyze the views of contemporary Muslim thinkers such as Ismail Raji al-Faruqi and Syed Muhammad Naquib al-Attas regarding the concept of the Islamization of science, as well as explore the challenges and opportunities in its application. The research was conducted using a literature review method, examining relevant scholarly articles, books, and conference papers. The findings show that the Islamization of science offers a more holistic paradigm, where scientific knowledge is not only focused on empirical aspects but also considers ethical and moral dimensions. Despite facing several challenges, particularly in educational systems, the Islamization of science has significant potential to shape ethical and sustainable scientific knowledge. Thus, this concept is relevant in the context of the development of modern scientific knowledge in the Muslim world.